Dasar Pertimbangan Hakim dalam Memutus Tindak Pidana Perkosaan yang Dilakukan oleh Anak - Imam Slamet; Setiyono Setiyono (University of Merdeka Malang, 2018)
Children as the next generation need guidance both for growth and physical, mental, sausage and protection development that will endanger them and the nation in the future. Protection of girls is very important because there are many cases of rape of women. The problems that will be examined in this study, namely: What are the factors that encourage children to commit rape crimes? and What is the basis of consideration for judges in imposing criminal decisions on children who commit rape crimes? This study uses normative-empirical research. Factors that encourage children to commit rape crimes include: psychological factors, family factors and environmental factors and economic factors, therefore all existing components must be involved in the development and development of children, so that children do not do deeds from the norm -the existing status. A child judge in making a decision on a child who commits a rape crime bases consideration on a juridical foundation, in the form of legislation related to a criminal act committed by a child. The judge may not drop the cumulative sentence, and limit the maximum sentence imposed.How to cite item: Slamet, I., Setiyono, S. (2018). Dasar Pertimbangan Hakim dalam Memutus Tindak Pidana Perkosaan yang Dilakukan oleh Anak. Jurnal Cakrawala Hukum, 9(1), 40-49. doi:https://doi.org/10.26905/idjch.v9i1.2209